Plasma in the near Venus tail: Venus Express observations. Issue 12 (9th December 2013) - Dubinin, E.; Fraenz, M.; Zhang, T. L.; Woch, J.; Wei, Y.; Fedorov, A.; Barabash, S.; Lundin, R.
<x xml:space="preserve">Abstract</x> [1] Although Venus has no global intrinsic magnetic fields, it possesses a long magnetotail of induced origin. The topology of the tail is determined by the interplanetary magnetic field orientation. We present recent plasma and magnetic field observations in the near Venus tail (X≥−3RV) made by the Venus Express spacecraft. We show that ion acceleration in the Venus plasma sheet is produced by the slingshot effect of the draping magnetic field lines, though some features as differential streaming of different ion species point to the existence of other forces. We explain a bell shape of ion spectrograms while the spacecraft crosses the current sheet. The absence of a balance between the lobe magnetic pressure and thermal pressure of plasma in the plasma sheet indicates a dynamic rather than a static equilibrium in the Venus magnetotail. A strong asymmetry of the plasma sheet is controlled by the direction of the motional electric field in the upstream solar wind. In the hemisphere pointed in the direction of the motional electric field, the j×B force accelerates plasma tailward supplying the plasma sheet, while in the opposite hemisphere, the flow pattern occurs less regularly with smaller speeds but higher number densities.